EFL Students’ Challenges towards Home Learning Policy During Covid-19 Outbreak - Ariyanti Ariyanti (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
Obviously, the world wide is shocking with pandemic of Covid-19 where it effects to every single part of human lives and everyday activities for sure. Additionally, the Covid-19 pandemic also has its influence toward education system from lower to upper levels. Both teachers and students feel the impact from the recent pandemic especially in Indonesian context where of course it triggers barriers due to the educational adjustment they have to follow. Therefore, this research is particulalrly aimed to investigate perception of EFL students toward home learning during pandemic of Covid-19. In-dept interview was applied to eight students of English Department students of University of Widya Gama Mahakam Samarinda. Specifically, the in-dept interview is consisted of the students’ perception mainly regarding with challenges they faced when having home learning activities during the Covid-19 pandemic up to the recent time. As a result, the researcher found that the students face three major types of challenges including internet connection, healthy reason, and the use of certain online application. Further discussion and and fruitful suggestions also provided in this research.